RISK ASSESSMENT IN GAS DISTRIBUTION NETWORK LEAKS USING THE PRELIMINARY RISK ANALYSIS AND EISENBERG VULNERABILITY METHOD - Heracleto DOS SANTOS; Guozhong HUANG; Xuehong GAO (Transactions of the VŠB: Technical University of Ostrava, Safety Engineering Series, 2023)
The natural gas distribution system is made up of an extensive network of pipelines and some equipment such as regulators, valves, filters, meters and converters that require maintenance to maintain operation and identify any gas leaks in advance. The risk analysis process is widely used in the gas industries to locate faults in operations and processes that could cause accidental release of chemicals, fire or explosion and to provide decisions to improve operational risk safety. It was concluded that for risk analysis (PRA) accidents occur due to lack of maintenance in the facilities and equipment set and the Eisenberg Vulnerability Method provided an assessment of the probability of damage to infrastructure and damage to the environment for 1%, 50% and 99% lethality.